Geoecoprotective Properties of Cement and Concrete Against Heavy Metal Ions. (2015) - Svatovskaya, Larisa; Shershneva, Maria; Baydarashvily, Marina; Sychova, Anastasia; Sychov, Maxim; Gravit, Marina
Abstract: Geoecoprotective properties of the binder system are discussed in the paper. The base of such properties is detoxication of environment from heavy metal ions by means of reactions with silicate and sulphate calcium. Thermodynamic analysis of the systems has shown that reactions of heavy metal ions (HMI) with certain building materials provides reduction of Gibbs energy value comparing to hydration reactions without HMI. Detoxicating systems were named mineral geoantidotes (MGA). Estimations of the detoxication processes and application examples are given.